DEVELOPMENT STRATEGIES FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSME) BY IMPROVING THE QUALITY OF HUMAN RESOURCES - Ahmad Mukhlis; Anoesyirwan Moeins; Widodo Sunaryo (Yayasan Education and Social Center, 2022)
MSMEs, which stand for micro, small, and medium enterprises, play a significant part in the expansion of the Indonesian economy. The contribution of micro, small, and medium-sized enterprises (MSMEs) to economic growth in Indonesia is undeniable; however, despite this, MSMEs continue to struggle with a wide variety of internal and external challenges. Consequently, it is essential to have an MSME development strategy to make MSMEs more developed. In the meantime, the problem that frequently arises in micro, small, and medium-sized enterprises (MSMEs) is the low quality of the human resources. The quality of a company's human resources is a significant factor in determining whether it will achieve success or failure. Human resources are an essential component of any business. Therefore, one must access competent human resources to cultivate a successful business. This research aims to establish a plan for the growth of micro, small, and medium-sized enterprises (MSME) of kerupuk cracers in the city of Serang by enhancing the caliber of the human resources used in their management. Methods of qualitative research used for this study. In this research project, the data collection methods include observations, interviews, and documentation. The data analysis process carries out in several stages, the most important of which are data reduction, data presentation, and conclusions. According to the findings, there were three different routes to enhance the quality of the human resources available at MSME Crackers in Serang City. 1) Training, with an emphasis on both